Analysis of Questioning Skills through Science Learning Practices in Microteaching Courses - Asti, Nur Riya; Ngazizah, Nur (Islamic Journal of Integrated Science Education (IJISE), 2022)
Study aims to describe the mastery of the questioning skills of prospective elementary school teacher students at the Purworejo Muhammadiyah UniversitySources of data in this study were student teacher candidates for elementar school in Muhammadiyah University. The data collection technique used is observation. The analysis used in this research is qualitative data analysis. The indicators of mastery of questioning skills include basic questioning skills and advanced questioning skills. The results showed that Prospective elementary school teacher students at Purworejo Muhammadiyah University had more mastery of basic questioning skills compared to advanced questioning skills. The data were obtained by using the observation method on micro learning activities by Prospective elementary school teacher students at Purworejo Muhammadiyah University. The basic teaching skills, especially the questioning skills, were analyzed and observed directly in the implementation of microteaching activities. Based on the research that has been done, it is found that the mastery of basic skills in teaching is very necessary, especially the skills in asking questions. Asking is a verbal utterance that asks for a response from someone you know. Responses can be in the form of knowledge or things that are the result of consideration.